The story vs the storyteller: Factors associated with the effectiveness of brief video‐recorded patient stories for promoting opioid tapering - Stephen G. Henry; Bo Feng; Susan Verba; Richard L. Kravitz; Ana‐Maria Iosif (Wiley, 2021)
Abstract Background Narrative communication is often more persuasive for promoting health behaviour change than communication using facts and figures; the extent to which narrative persuasiveness is due to patients' identification with the storyteller vs engagement with the story is unclear. Objective To examine the relative impacts of patient engagement, age concordance and gender concordance on perceived persuasiveness of video‐recorded narrative clips about opioid tapering. Methods Patient raters watched and rated 48 brief video‐recorded clips featuring 1 of 7 different storytellers describing their experiences with opioid tapering. The dependent variable was clips' perceived persuasiveness for encouraging patients to consider opioid tapering. Independent variables were rater engagement with the clip, rater‐storyteller gender concordance and rater‐storyteller age concordance (<60 vs ≥60). Covariates were rater beliefs about opioids and opioid tapering, clip duration and clip theme. Mixed‐effects models accounted for raters viewing multiple clips and clips nested within storytellers. Results In multivariable models, higher rater engagement with the clip was associated with higher perceived persuasiveness (coefficient = 0.46, 95% CI 0.39‐0.53, P < .001). Neither age concordance nor gender concordance significantly predicted perceived persuasiveness. The theme Problems with opioids also predicted perceived persuasiveness. Conclusion Highly engaging, clinically relevant stories are likely persuasive to patients regardless of the match between patient and storyteller age and gender. When using patient stories in tools to promote health behaviour change, stories that are clinically relevant and engaging are likely to be persuasive regardless of storytellers' demographics. Patient or public contribution Patients were involved as storytellers (in each clip) and assessed the key study variables.